UJI AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT PISANG KAPAS (Musa paradisiaca L.) DENGAN METODE FRAP DAN DPPH PADA SEDIAAN HAND AND BODY LOTION - Risna Adhi Yulianti; Slamet 93 Ffua; Dwi Bagus Pambudi; Wulan Agustin Ningrum (Media Informasi, 2022)
ABSTRACT Degenerative diseases are often found in people in ndonesia, such as cancer, atherosclerosis, rheumatism, coronary heart disease, cataracts and diabetes mellitus. One of the causes of degenerative diseases is free radicals. Antioxidants are compounds that can neutralize free radicals by donating their electrons to free radical compounds. One of the bioactive compounds that have a role as antioxidant activity is favonoids. Many flavonoid compounds are contained in the yellow skin of ripe bananas. The purpose of this study was to determine the antioxidant activity of cotton banana skin in hand and body lotion preparations. This antioxidant analysis used the FRAP and DPPH methods and the determination of total phenol content and total flavonoid content. In the phytochemical screening test, cotton banana skin extract showed positive phenolic compounds, flavonoids, saponins, terpenoids and tannins. The results of the measurement of total phenol were 28.225 mg GAE/g extract, while the total flavonoid value was 69.26 mg QE/g exiract. The measurement results of the antioxidant activity of the cotton banana skin cxtract (Musa paradisiaca L.) using the FRAP method were 368,700=1 mol Fe2+/g extract and the DPPH method obtained an IC50 value of 13.169 g/mL. In the hand and body lotion preparation, the highest antioxidant activity was found in formula 3, namely 1958,033 + 8,08 mol Fe2+/g and the IC50 value was 2,417 g/mL. The results were statistically analyzed using analysis of variance (ANOVA) then Tukey's test was performed which yielded a value of 0.05 indicating that there were differences in the antioxidant activity of the extract samples in the FRAP method and the DPPH method.